LRC and WMC Retention Report by First-Time, Full-Time First-Year Cohorts Fall 2021 and Fall 2022 - Sohui Lee::::::; Brook Masters:::::: (2022)
This report displays and explains three tables of data on retention rates provided by Institutional Research on cohorts of first-time, full-time, first-year CSUCI students (Fall 2021 and Fall 2022). This report compares retention rates for students who visited either the LRC or WMC with the retention rates of students who did not visit either center. The overall analysis reveals a higher retention rate for students who visit either center with the greatest benefits occurring for the HUG student population.